Isolation, morphometry, and culture of Colurella sp. (Rotifera: Ploimida) - Letsoin, Petrus P; Pangkey, Henneke; Sampekalo, Julius; Rumengan, Inneke F.M; Wullur, Stenly; Rimper, Joice R.S.T.L (Graduate Program of Sam Ratulangi University, 2013)
The rotifer Brachionus rotundiformis (total body length 240.59±10.24 μm, lorica length 175.28±9.18 μm, and lorica width 124.28±7.76μm) is commonly used as starter food in the larval rearing of marine fish. But, larvae of some marine tropical fish species required starter food with body size smaller than B. rotundiformis. The present study was aimed to isolate minute rotifers from nature and to assess the possibility of culturing these rotifers. Sampling of rotifers was conducted in an estuary of Mangket (Kema-Minut), using plankton net (mesh size 40 µm). A trial of culturing the rotifers was conducted at salinities of 10, 20 and 30 ppt by using a microalga, Nannochloropsis oculata. A species of rotifer identified as Colurella sp. (family Lepadellidae) was successfully isolated from the sampling location. Body size of Colurella sp. was extremely small (Total length 123.22±5.45 μm, lorica length 95.96±3.81 μm, and lorica width 53.57±3.11 μm), which were smaller than Brachionus rotundiformis SS-type as a conventional starter food for marine fish larvae. Results of culturing the minute rotifer Colurella sp. showed that the species grew well at salinities of 10, 20 and 30 ppt with no significant difference among treatments (ANOVA, p>0.05), indicating a potential use of minute rotifer Colurellasp. as starter food for marine fish larvae. Rotifera Branchionus rotundiformis (ukuran tubuh: panjang total 240,59±10,24 μm, panjang lorika 175,28±9,18 μm, dan lebar lorika 124,28±7,76μm) sering digunakan sebagai pakan awal pemeliharaan larva ikan laut. Namun, larva beberapa spesis ikan laut tropis membutuhkan pakan awal berukuran tubuh lebih kecil dari Branchionus rotundiformis. Penelitian ini bertujuan untuk mendapatkan minute rotifer dari alam (berukuran tubuh lebih kecil dari B. rotundiformis) dan menguji kemungkinan pemeliharaannya. Sampling rotifer dilakukan di perairan estuari Desa Mangket (Kema-Minut), menggunakan plankton net (ukuran mata jaring 40 µm). Uji coba pemeliharaan dilakukan pada salinitas (10, 20, dan 30 ppt) dengan menggunakan Nannochloropsis oculata. Satu spesies minute rotifer yang teridentifikasi sebagai Colurella sp. (family Lepadellidae) berhasil diisolasi dari lokasi sampling. Colurella sp. memiliki ukuran tubuh sangat kecil (panjang total [PT] 123,22±5,45 µm, panjang lorika [PL] 95,96±3,81 µm, dan lebar lorik [LL] 53,57±3,11 µm) yang mana lebih kecil dari Branchionus rotundiformis tipe-SS sebagai pakan awal larva ikan laut. Hasil uji coba pemeliharaan minute rotifer Colurella sp. menunjukkan bahwa spesis ini dapat tumbuh pada salinitas 10, 20, dan 30 ppt dengan perbedaan kepadatan populasi yang tidak signifikan antar perlakuan (Uji ANOVA, p > 0.05) mengindikasikan potensi pemanfaatan minute rotifer Colurella sp. sebagai pakan awal larva ikan laut.